Soil solarization for managing weeds in brinjal (Solanum melongena) nursery - MAHAJAN, GULSHAN; SINGH, KG; BHATIA, R K; KUMAR, ASHWANI (The Indian Journal of Agricultural Sciences, 2011)
Soil solarization is a technique used for weed control in regions with high level ofsolar radiations. Soil solarization for 35 or 45 days decreased the emergence of annual weeds by over 90 %. Elnergence of Cyperus rotundus from tubers was increased by soil solarization. FUlihennore, seed gennination of Conunelina benghalensis was increased by soil solarization. The ll1ain solarization effect was restricted to 0 - 5 em layer of the soil. The maximum temperature at 5em depth was about 8 - 10°C wanner in solarized soil than in controi plots. It was concluded that soil solarization with transparent polyethylene film for 35 or 45 days caused healthy seedling of brinjal by increasing the dry matter production ofseedlings and proved very useful technique for controlling more than half of the weed species recorded without any use ofchemical. 35 or 45 days decreased the emergence of annual weeds by over 90 %. Elnergence of Cyperus rotundus from tubers was increased by soil solarization. FUlihennore, seed gennination of Conunelina benghalensis was increased by soil solarization. The ll1ain solarization effect was restricted to 0 - 5 em layer of the soil. The maximum temperature at 5em depth was about 8 - 10°C wanner in solarized soil than in controi plots. It was concluded that soil solarization with transparent polyethylene film for 35 or 45 days caused healthy seedling of brinjal by increasing the dry matter production ofseedlings and proved very useful technique for controlling more than half of the weed species recorded without any use ofchemical. 35 or 45 days decreased the emergence of annual weeds by over 90 %. Elnergence of Cyperus rotundus from tubers was increased by soil solarization. FUlihennore, seed gennination of Conunelina benghalensis was increased by soil solarization. The ll1ain solarization effect was restricted to 0 - 5 em layer of the soil. The maximum temperature at 5em depth was about 8 - 10°C wanner in solarized soil than in controi plots. It was concluded that soil solarization with transparent polyethylene film for 35 or 45 days caused healthy seedling of brinjal by increasing the dry matter production ofseedlings and proved very useful technique for controlling more than half of the weed species recorded without any use ofchemical.